Development of HOTS-Based Evaluation Instruments to Improve Students' Critical Thinking Skills - Idris Idris; Maria Sari Siregar; Widayatul Eko Santoso; Mustaqim Hasan (Global Education Journal, 2026)
The development of Higher Order Thinking Skills (HOTS)-based evaluation instruments in education is a strategic effort to improve the quality of learning processes and outcomes. This study aims to analyze the development of Higher Order Thinking Skills (HOTS)-based evaluation instruments in improving students' critical thinking skills and to formulate a systematic, contextual, and applicable conceptual framework for developing evaluation instruments. The research employed a qualitative approach using the library research method through a review of various relevant sources, including academic books, national and international journal articles, and previous studies related to learning evaluation, HOTS, and critical thinking skills. Data analysis was conducted using content analysis techniques through the processes of identification, categorization, interpretation, and synthesis of various findings from the literature. The results indicate that the development of HOTS-based evaluation instruments should be carried out regularly through several stages, including needs analysis, formulation of critical thinking indicators, development of contextual stimulus-based questions, instrument validation, and quality testing. The study also reveals that HOTS-based evaluation instruments function not only as tools for measuring learning outcomes but also as learning strategies to develop students' abilities in analysis, evaluation, problem-solving, and critical thinking. This study contributes by formulating a conceptual framework for HOTS-based evaluation instrument development that can serve as a reference in creating more innovative learning evaluation systems oriented toward developing 21st-century competencies.